Covalent polyphenols-proteins interactions in food processing: formation mechanisms, quantification methods, bioactive effects, and applications - Zhang, Kangyi; Huang, Jinbao; Wang, Dongxu; Wan, Xiaochun; Wang, Yijun (Frontiers in Nutrition, 2024)
Proteins and polyphenols are abundant in the daily diet of humans and their interactions influence, among other things, the texture, flavor, and bioaccessibility of food. There are two types of interactions between them: non-covalent interactions and covalent interactions, the latter being irreversible and more powerful. In this review, we systematically summarized advances in the investigation of possible mechanism underlying covalent polyphenols-proteins interaction in food processing, effect of different processing methods on covalent interaction, methods for characterizing covalent complexes, and impacts of covalent interactions on protein structure, function and nutritional value, as well as potential bioavailability of polyphenols. In terms of health promotion of the prepared covalent complexes, health effects such as antioxidant, hypoglycemic, regulation of intestinal microbiota and regulation of allergic reactions have been summarized. Also, the possible applications in food industry, especially as foaming agents, emulsifiers and nanomaterials have also been discussed. In order to offer directions for novel research on their interactions in food systems, nutritional value, and health properties in vivo, we considered the present challenges and future perspectives of the topic.